Determinants of job satisfaction of doctors and nurses in organised settings (hospitals and health centres) in Muscat Governorate, Sultanate of Oman - Al Shafaee, Mohammed Ali Mohammed (2001)
Oman has inadequate health manpower, particularly doctors and nurses, as evident from the limited prospect for Omanization (employment of Omani nationals). Medical services in Oman have relied primarily on the recruitment of expatriate doctors and nurses from several countries. The solution to the present shortage in health professionals (doctors and nurses) is complex, but if we identify those factors that health professionals perceive as negative, because they contribute to dissatisfaction and turnover, possible interventions to improve working conditions may be developed. Therefore, this study aimed to examine the factors affecting job satisfaction of doctors and nurses, including differences in those factors related to nationality (Omani and non- Omani) and organisations. Three hospitals and three primary care health centres in Muscat Governorate were selected for the study. Job satisfaction was explored qualitatively via focus group interviews and quantitatively, using survey questionnaires. The job satisfaction questionnaires were based mainly on the instrument developed by Stamps et al. (1978). Factor analysis was employed to ascertain factors underlying job satisfaction. Several organisational and job-related factors were found to influence job satisfaction of both doctors and nurses: relationships with colleagues and teamwork, professional status, relationship with patients, administration, workload, pay, promotion, working conditions and medical stress. Doctors' job satisfaction was statistically significantly associated with their age, marital status, designation, work experience and weekly working hours. Nurses' job satisfaction was statistically significantly associated with their total years of work experience in Oman. There was a statistically significant difference in job satisfaction between Omani and non-Omani i doctors. Additionally, there were statistically significant differences in job satisfaction between doctors/nurses working in different organisations. The findings suggest a need to re-evaluate salary scales, reward loyalty and performance with promotion, improve the management skills of medical and nursing administrators, improve the on-call schedules for doctors and reduce the non-nursing tasks for nurses. They also indicate a need to improve the quality and availability of postgraduate training programmes for doctors
HydraID: hull:5405 Hydra Discover Access Group: public EThOS identifer: 395522 ETD Collection: ETDMedicine
Keywords: Medicine